GETTING PAST NATURE AS A GUIDE TO THE HUMAN SEX RATIO - Murphy, Timothy F. (Bioethics, 2013)
Sex selection of children by pre-conception and post-conception techniques remains morally controversial and even illegal in some jurisdictions. Among other things, some critics fear that sex selection will distort the sex ratio, making opposite-sex relationships more difficult to secure, while other critics worry that sex selection will tilt some nations toward military aggression. The human sex ratio varies depending on how one estimates it; there is certainly no one-to-one correspondence between males and females either at birth or across the human lifespan. Complications about who qualifies as ‘male’ and ‘female’ complicate judgments about the ratio even further. Even a judiciously estimated sex ratio does not have, however, the kind of normative status that requires society to refrain from antenatal sex selection. Some societies exhibit lopsided sex ratios as a consequence of social policies and practices, and pragmatic estimates of social needs are a better guide to what the sex ratio should be, as against looking to ‘nature’. The natural sex ratio cannot be a sound moral basis for prohibiting parents from selecting the sex of their children, since it ultimately lacks any normative meaning for social choices.